2011
DOI: 10.1021/cm201330x
|View full text |Cite
|
Sign up to set email alerts
|

Multi-temperature Synchrotron Powder X-ray Diffraction Study and Hirshfeld Surface Analysis of Chemical Bonding in the Thermoelectric Zintl Phase Yb14MnSb11

Abstract: Table of contents: 1. Full details on Rietveld refinements of Yb 14 MnSb 11 , 90-900K 2. Debye-fits of Uiso(T) for Yb 14 MnSb 11 . 3. Various bond distances in Yb 14 MnSb 11 4. PXRD data of Yb 14 MnSb 11 at 400K, 550K and 700K 5. Atomic Hirshfeld surfaces of Yb 14 MnSb 11 6. Comparison of high and low temperature AHS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…While Ce was only observed on the Yb(2) site for x = 0.32, samples with x = 0.45 and higher show Ce both on the Yb (2) and Yb (4) volume followed by Yb(4), while Yb(1) and Yb(3) have the smallest volumes. 24 Previous work on Eu 13 AMnSb 11 showed that smaller ions such as Ca and Yb prefer to substitute on the Eu(3) and Eu(1) sites while larger ions such as Ba and Sr prefer to substitute on the Eu(2) and Eu(4) sites, 25 respectively, consistent with the Hirshfeld analysis. Since Ce 3+ is similar in size to Yb 2+ , it is surprising that it has such a strong preference for the Yb(2) and Yb (4) Temperature-dependent molar susceptibility data from single crystals with x = 0-0.58 are shown in Figure 3(a) in the temperature range where ferromagnetic ordering is observed.…”
Section: +supporting
confidence: 57%
“…While Ce was only observed on the Yb(2) site for x = 0.32, samples with x = 0.45 and higher show Ce both on the Yb (2) and Yb (4) volume followed by Yb(4), while Yb(1) and Yb(3) have the smallest volumes. 24 Previous work on Eu 13 AMnSb 11 showed that smaller ions such as Ca and Yb prefer to substitute on the Eu(3) and Eu(1) sites while larger ions such as Ba and Sr prefer to substitute on the Eu(2) and Eu(4) sites, 25 respectively, consistent with the Hirshfeld analysis. Since Ce 3+ is similar in size to Yb 2+ , it is surprising that it has such a strong preference for the Yb(2) and Yb (4) Temperature-dependent molar susceptibility data from single crystals with x = 0-0.58 are shown in Figure 3(a) in the temperature range where ferromagnetic ordering is observed.…”
Section: +supporting
confidence: 57%
“…3), and the values are also in good agreement with published values. 30 The Bragg R B and the R f factor of the profile matching were 0.3 and 0.4%, respectively, for all temperatures. A density, ρ, of 8.35(2) g/cm 3 was obtained from the lattice parameter at 300 K. The thermal expansion coefficient, α, was obtained from a model of the temperature dependence of the lattice parameter a, with a third-order polynomial function, a m (T ), in order to reduce noise in the data and by using α a = [da m (T )/dT ]/a m (300 K); see Fig.…”
Section: A Structurementioning
confidence: 86%
“…Recently, the mean square displacements were refined from x-ray diffraction patterns and published in Ref. 30.…”
Section: A Structurementioning
confidence: 99%
“…The maximum amount of each RE substituted for Yb was determined to be 0.7 for La, 0.6 for Ce, and 0.5 for Tm [5][6][7][8]. Microprobe analysis of the crystals of Yb 14-x Gd 0x MnSb 11 of which properties were measured provided the following compositions (Table 1) showing that the maximum amount of Gd that can substitute for Yb in Yb 14-x Gd x MnSb 11 is x = 0.48.As data show (Tables 2-4) maximum introduction of does not exceed х=0.…”
Section: Icnms 2016mentioning
confidence: 99%
“…All these three parameters are interlinked and one is optimized at the expense of others.Solidsolutions with lanthanum, cerium, thulium, lutetium (partial replacement of ytterbium) [6][7][8][9][10][11], with aluminum (replacement of manganese) [12], germanium, tellurium (partial replacement of antimony) [13,14] have been investigated with an aim towards increasing zT.…”
Section: Introductionmentioning
confidence: 99%